"Now walks like others": a preliminary enquiry into the Northampton Crippled Children's Fund. (29th September 2015) - Chan, C; Reinarz, J; Natarajan, R; Williams, A
Abstract : Interest into the history of child health and disability has intensified over the years. However, it is a relatively recent and unresearched area and still in its early development. Care available to poor, "crippled children" in Victorian England is a generally unexplored subject. Before the introduction of universal free access to healthcare, there was little available for those unable to afford it, beside voluntary organisations. One such example was the Northampton Crippled Children's Fund (NCCF), which from 1893 to 1925, provided care to the "crippled children" of the town. It funded medical and surgical care for children with deformities. Besides operations (which were rare), it also provided surgical boots, carriages and nourishment as well as providing an annual holiday to its seaside "colony" in Llandudno. Primary sources concerning disabled people in history are difficult to find and the study of disability history is challenging. However, this presentation using primary sources from the Archive, Northampton General Hospital will reconstruct such voluntary healthcare provided to "Crippled Children in straightened circumstances living in the town of Northampton under 17 years of age." NCCF annual reports from 1905 to 1925 include records of treatments, their costs and their dates given to each named child. Within the record books, some individual cases also include early x-rays, hand drawn vignettes pre and post treatment, together with relevant newspaper cuttings. The 1911 census online is also used. In a consecutive case series of twenty children randomly taken from a NCCF record book, the recorded pathologies were: nine rickets (45%), four spinal pathology (20%), three tuberculosis (15%), two paralysis (10%), one hemiplegia (5%), and one carcinoma (5%). Treatments were mainly medical, involving surgical boots but rarely surgical. The NCCF material provides insight into child health and disability and shows considerable potential for further exploration by social and medical historians. Lastly, the NCCF material will also be examined alongside that of other contemporary Charities such as the Birmingham's Cripples Union, which was founded in 1896. Although there have been considerable advances in clinical science since the early nineteenth century, many of these conditions remain considerable therapeutic challenges in the early twenty-first century.